THE EFFECT OF STUDENTS’ ACHIEVEMENT IN STUDYING VOCABULARY THROUGH SCRAMBLE METHOD AT SMP N 1 KUALUH HULU - Ismi Yulizar (Tarbiyah bil Qalam : Jurnal Pendidikan Agama dan Sains, 2022)
The Aim of this research is to know whether any significant effect of studying vocabulary through scramble method. Thisresearch is an experimentalresearch. The population of this research was the eighth grade students of SMP N 1 Kualuh hulu in academic year 2018/2019. The total number of the population was 276 students. In this case 78 students were taken as the samples. These samples were divided into two groups. The first group was an experimental group which was taught by using Scramble Method and the second group was control group which was taught without using Scramble method or using conventional technique. This research used the quantitative data. The quantitative data were analyzed by using test of word scramble was consisted of 5 items, filling letters in box was consisted of 5 items and guessing the picture was consisted 10 items. The calculation of the reliability of the test shows that the reliability is sufficient (0,5). The data were analyzed by using t-test. The result of calculating the t-test shows that t observed is higher than t table 8,18 > 1,66 (p = 0,05) with df 76. t observed> t value> t table. 8,18 > 2,36 > 1,66. It could be concluded that Ha is accepted. It means that there is significant effect of scramble method on Students’ Achievement in Studying Vocabulary.